Brand Management - Fíla, Petr; Harantová, Monika; Hesková, Marie, 1948-; Vysoká škola ekonomická v Praze. Fakulta managementu (2018)
The bachelor thesis on Brand Management topic is focused on solving given problems in specific conditions of economic practice and on the basis of the theoretical and methodological knowledge, obtained by studying professional literature from the area and their subsequent application into the Czech company EYELEVEL, s.r.o.
Vedoucí práce: Monika Harantová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta managementu, 2018
Obsahuje bibliografii
Rok obhajoby 2018
Keywords: obchodní značky; řízení značky; oceňování obchodní značky; management [obor bakal. práce]; bakalářské práce; brand name products; brand management; valuation of brand name products; bachelor's theses